Interpretation the Hepatotoxicity Based on Pharmacokinetics Investigated Through Oral Administrated Different Extraction Parts of Polygonum multiflorum on Rats - Zhang, Miao; Lin, Longfei; Lin, Hongmei; Qu, Changhai; Yan, Lei; Ni, Jian (Frontiers in Pharmacology, 2018)
The liver injury induced by Polygonum multiﬂorum (PM) used for clinical treatment has recently received widespread attention. This study aimed to determine the hepatotoxicity of PM through pharmacokinetics studies. The extract of PM was separated to isolate the anthraquinone fraction, the tannin and polysaccharide fraction, the hydroxystilbene fraction, and the combined anthraquinone fraction. A rapid LC-MS/MS method was developed and validated to simultaneously analyze 2,3,5,4'-tetrahydroxystilbene-2-O-β-glucoside (TSG), emodin-8-O-β-D-glucopyranoside (EDG), and emodin in rat plasma, and was applied to the pharmacokinetics (PK) studies. The hepatotoxicity of different extracted parts of PM was evaluated through the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), total bilirubin (TBil), direct bilirubin (DBil), and indirect bilirubin (IBil) in rat serum. The results showed that liver injury occurred in all the treated groups and that the hepatotoxicity performance of the total extract was different from other groups. The pharmacokinetic studies showed that the Cmax, Tmax, AUC, t1/2, and MRT of the major compounds of different extracted parts were significantly different in rat plasma at same dosage. Emodin-O-hex-sulphate, tetrahydroxystilbene-O-(galloyl)-hex, emodin (original and generated through EDG deglycosylation), and other free anthraquinones might be responsible for the hepatotoxicity of PM in vivo. PM extracts produced inhibitory effects on drug metabolic enzymes, include CYP3A4, CYP2C19, CYP2E1, UGT1A1.etc. And these effects may be related to its hepatotoxicity and pharmacokinetic behavior different. This information on hepatotoxicity and the pharmacokinetic comparison may be useful to understand the toxicological effects of PM.